Streaming Torque with Turbulent Diffusion - Qiang Hou; Cong Yu (The Astrophysical Journal)
Fast type I migration of (proto)planets poses a challenging problem for the core accretion formation scenario. We found that the dust-induced “Streaming Torque” (ST) may slow down or even reverse the planet migration in Q. Hou & C. Yu. But in realistic protoplanetary disks, dust diffusion induced by gas turbulence may have important influences on ST. We perform linear analysis to investigate the effects of dust diffusion on ST. The dependence of ST on dust diffusion may provide better constraints on the turbulence strength and the stopping time τ . We derive the dispersion relation for all the wave modes in the two-fluid system. The dust diffusion will smooth the short-wavelength structure of the the quasi-drift mode and split it into two predominant D-drift modes with opposite directions. The outgoing D-drift mode will contribute to a negative torque on planets, particularly when τ  ∼ 0.1, which slightly shifts the zero-torque turning point. We explore how ST depends on the regimes of aerodynamic drag, dust mass fraction, and disk scale height. We compare the radial wavenumbers of D-drift modes under different formulations of dust diffusion and find qualitative agreement. In all cases, τ at the zero-torque turning point, which determines the direction of planetary migration, consistently remains on the order of ∼0.1, corresponding to large pebble-sized dust grains. This suggests that rapid dust coagulation can inhibit the inward migration of planets, implying that weak gas turbulence may enhance the survival of protoplanets.